Vortioxetine Differentially Modulates MK-801-Induced Changes in Visual Signal Detection Task Performance and Locomotor Activity - Hillhouse, Todd M.; Merritt, Christina R.; Smith, Douglas A.; Cajina, Manuel; Sanchez, Connie; Porter, Joseph H.; Pehrson, Alan L. (Frontiers in Pharmacology, 2018)
Attention impairment is a common feature of Major Depressive Disorder (MDD), and MDD-associated cognitive dysfunction may play an important role in determining functional status among this patient population. Vortioxetine is a multimodal antidepressant that may improve some aspects of cognitive function in MDD patients, and may indirectly increase glutamate neurotransmission in brain regions classically associated with attention function. Previous nonclinical research suggests that vortioxetine has limited effects on attention. This laboratory previously found that vortioxetine did not improve attention function in animals impaired by acute scopolamine administration, using the visual signal detection task (VSDT). However, vortioxetine has limited effects on acetylcholinergic neurotransmission, and thus it is possible that attention impaired by other mechanisms would be attenuated by vortioxetine. This study sought to investigate whether acute vortioxetine administration can attenuate VSDT impairments and hyperlocomotion induced by the noncompetitive N-methyl-D-aspartate (NMDA) receptor antagonist MK-801. We found that acute vortioxetine administration had no effect on VSDT performance on its own, but potentiated MK-801-induced VSDT impairments. Furthermore, vortioxetine had no effect on locomotor activity on its own, and did not alter MK-801-induced hyperlocomotion. We further investigated whether vortioxetine’s effect on MK-801 could be driven by a kinetic interaction, but found that plasma and brain exposure for vortioxetine and MK-801 were similar whether administered alone or in combination. Thus, it appears that vortioxetine selectively potentiates MK-801-induced impairments in attention without altering its effects on locomotion, and further that this interaction must be pharmacodynamic in nature. A theoretical mechanism for this interaction is discussed.